KEBIASAAN BURUK YANG MENIMBULKAN KARIES PADA SANTRI PONDOK PESANTREN (Politeknik Kesehatan Kemenkes Bandung, 2021)
Bad habits are behaviors that are carried out repeatedly and can cause damage or harm. One of the damage that bad habits can cause to teeth is caries. This study aimed to determine what bad habits were carried out by the Student of islamic Boarding School. This type of research is a descriptive study where the data will be processed and presented in a frequency distribution table. The subjects of this study were the Student of Islamic Boarding School. Sampling was carried out by purposive sampling and using the slovin formula so that one hundred samples were obtained from the student of Islamic Boarding School. Data collection in this study used questionnaires distributed to respondents online. The results showed that the bad habits that cause caries in the student of Islamic Boarding School are smoking, consuming cariogenic foods, mouth breathing, drinking soft drinks, bruxism and eating sweet foods.